Ecological niche and potential distribution of the endangered Bos javanicus in south-western Java, Indonesia - Rahman, Dede Aulia (THERYA, 2019)
Understanding the ecological niche and spatial distribution of wildlife species is important for the conserving and enhancing of biodiversity in a landscape system. Banteng (Bos javanicus) is a vital and important source of germplasm and protected by Indonesia law and considered to be Endangered under the International Union for Conservation of Nature list. During 2015 to 2017, surveys were undertaken on the largest population of wild banteng occurring in Ujung Kulon National Park. Data were gathered from a long-term camera trapping to assess the ecological niche and distribution of banteng using Maximum Entropy Modelling (Maxent) algorithm. Over a period of 30,149 trap nights there were high photo rates, indicating areas of high conservation importance for these species within the park. Distribution prediction indicated that habitat variables such as secondary forest, predation by Cuon alpinus and human impacts such as cultivated area and illegal activity, are critical to determining the habitat use of banteng. The results showed that banteng within the national park, mainly used the centre areas of the park with similar spatial use, both in wet and dry seasons. This study provides essential documentation of large Bovidae distribution in one of the four remaining habitats on Java, information for the development of management strategies within the park, and a basis upon which to develop future research on banteng.